Ab initio calculations of CaZrO3 (011) surfaces: systematic trends in polar (011) surface calculations of ABO3 perovskites - Eglitis, Roberts; Kleperis, Janis; Purans, Juris; Popov, Anatoli I.; Jia, Ran (Springer, 2020)
By means of the CRYSTAL computer program package, first-principles calculations of polar ZrO-, Ca- and O-terminated CaZrO3 (011) surfaces were performed. Our calculation results for polar CaZrO3 (011) surfaces are compared with the previous ab initio calculation results for ABO3 perovskite (011) and (001) surfaces. From the results of our hybrid B3LYP calculations, all upper-layer atoms on the ZrO-, Ca- and O-terminated CaZrO3 (011) surfaces relax inwards. The only exception from this systematic trend is outward relaxation of the oxygen atom on the ZrO-terminated CaZrO3 (011) surface. Different ZrO, Ca and O terminations of the CaZrO3 (011) surface lead to a quite different surface energies of 3.46, 1.49, and 2.08 eV. Our calculations predict a considerable increase in the Zr–O chemical bond covalency near the CaZrO3 (011) surface, both in the directions perpendicular to the surface (0.240e) as well as in the plane (0.138e), as compared to the CaZrO3 (001) surface (0.102e) and to the bulk (0.086e). Such increase in the B–O chemical bond population from the bulk towards the (001) and especially (011) surfaces is a systematic trend in all our eight calculated ABO3 perovskites. This work is licensed under a CC BY license.
Financial support via Latvian-Ukrainian Joint Research Project No. LV-UA/2018/2 for A. I. Popov, Latvian Council of Science Project No. 2018/2-0083 “Theoretical prediction of hybrid nanostructured photocatalytic materials for efficient water splitting” for R. I. Eglitis and J. Kleperis as well as ERAF project No. 1.1.1.1/18/A/073 for R. I. Eglitis and J. Purans is greatly acknowledged.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics